1992
DOI: 10.1159/000110942
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Ratio of Late Measles among Subacute Sclerosing Panencephalitis Patients in Karachi, Pakistan

Abstract: Subacute sclerosing panencephalitis (SSPE) in Western countries and Japan is found more often in early- than in late-measles sufferers. Recent SSPE findings in Karachi, however, present a different picture. Age at measles contraction was obtained and analyzed for 44 SSPE patients identified in Karachi between 1983 and 1988. The ratios of early- (< 2 years of age) and late- (> 2 years of age) measles sufferers among 36 of these patients who had experienced only one attack of measles were 0.33 and 0.67, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…1990). Similarly, after correcting for infant mortality, Takasu et al. (1992) in Karachi found an elevated proportion of late measles among SSPE patients in comparison to early measles preponderance among children in the general population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1990). Similarly, after correcting for infant mortality, Takasu et al. (1992) in Karachi found an elevated proportion of late measles among SSPE patients in comparison to early measles preponderance among children in the general population.…”
Section: Discussionmentioning
confidence: 94%
“…However, this epidemiological pattern may be different in developing countries in that both the male gender and early age of measles infection do not feature as consistent predisposing factors (Carman & Johnson 1989; Schoub et al. 1990; Takasu et al. 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Some authors believe that this is due to the immaturity of immune responses at that age that result in defective clearing of the viral infection (5,24). However, some reports, for example, one describing 36 patients from Karachi, Pakistan (25), have found that the primary infection occurred at an older age (although none in the Karachi study were older than age 9 at the time of their original measles).…”
Section: Age At Time Of Measles Exposurementioning
confidence: 99%
“…It has been reported that the incidence of subacute sclerosing panencephalitis (SSPE) is extremely high in Karachi, Pakistan as compared with that in western countries (1,2). To determine the risk factor(s) for the high incidence of SSPE in Karachi seems important to elucidate the mechanisms of the outbreak of SSPE, which have been discussed a great deal but are still unknown (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A long-term epidemiological survey has revealed the following two clear evidences associated with the high incidence of SSPE in Karachi. One is the high incidence of SSPE patients among those who are infected with measles virus after two years of age (2). The other is the relatively short incubation period from measles infection to onset of SSPE as compared with that in developed countries including Japan (6).…”
Section: Introductionmentioning
confidence: 99%